Two Cases of Cutaneous Adverse Effects Induced by Tumor Necrosis Factor-Alpha Inhibitors - Ena Masukawa; Yoshiaki Matsushima; Koji Habe; Keiichi Yamanaka (Karger Publishers, 2021)
Here, we report two cases of cutaneous adverse effects possibly induced by the use of tumor necrosis factor-alpha (TNF-α) inhibitors. The first case presented alopecia areata (AA) and atopic dermatitis (AD) that developed during the treatment of ulcerative colitis using infliximab; the other case presented urticaria and AD that developed during the treatment of rheumatoid arthritis using etanercept. AA, AD, and urticaria are relatively common skin diseases; however, they are not well known as adverse effects of TNF-α inhibitors. Although immunological studies were not performed, the clinical courses suggested that these skin disorders might have developed as a result of an immune four-way imbalance in T helper 1 (Th1), Th2, Th17, and regulatory T cells by the administration of TNF-α inhibitors.